2023
DOI: 10.3390/ijms24021155
|View full text |Cite
|
Sign up to set email alerts
|

Layer-Wise Relevance Analysis for Motif Recognition in the Activation Pathway of the β2-Adrenergic GPCR Receptor

Abstract: G-protein-coupled receptors (GPCRs) are cell membrane proteins of relevance as therapeutic targets, and are associated to the development of treatments for illnesses such as diabetes, Alzheimer’s, or even cancer. Therefore, comprehending the underlying mechanisms of the receptor functional properties is of particular interest in pharmacoproteomics and in disease therapy at large. Their interaction with ligands elicits multiple molecular rearrangements all along their structure, inducing activation pathways tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…Of these, 60 belong to the H1 region. This finding aligns with previous research [ 44 , 63 ], which also identified the influence of the H1 TM region in a model trained using random undersampling, with explanations generated through LRP. Additionally, in this study, residues from other regions such as ICL1, H2, H4, H5, ECL1, ECL2, and H7 are also shown to contribute in the prediction of conformational states, though in varying degrees and with distinct implications.…”
Section: Discussionsupporting
confidence: 91%
“…Of these, 60 belong to the H1 region. This finding aligns with previous research [ 44 , 63 ], which also identified the influence of the H1 TM region in a model trained using random undersampling, with explanations generated through LRP. Additionally, in this study, residues from other regions such as ICL1, H2, H4, H5, ECL1, ECL2, and H7 are also shown to contribute in the prediction of conformational states, though in varying degrees and with distinct implications.…”
Section: Discussionsupporting
confidence: 91%